EXAMINING THE OUTREACH OF ISLAMIC CHARITY BASED MICROFINANCE PROGRAMMES: EMPIRICAL EVIDENCE FROM INDONESIA - Aimatul Yumna; Matthew Clarke (Bank Indonesia, 2019)
One of the advantages of using Islamic social funds is the increased ability of microfinance institutions to provide financial services to the poor. This study aims to (1) investigates the characteristics of the clients of the Islamic Charity Based Microfinance (ICBM) program; (2) test whether the clients ICBM program are more vulnerable than the non clients group (3) discuss the rationale of why poor excluded from the zakat based microfinance program. The study was conducted in the microfinance program at zakat institutions namely Baitul Maal Muamalat (BMMI), BAZNAS, and Baitul Maal Beringharjo (BMB). A total of 236 respondents including clients and non-clients of three case study institutions were participated in this study. The data is analyzed using binomial logit model to evaluate factors affecting clients participation in ICBM programs in Indonesia. The findings show that clients and non-clients of ICBM have a similar demographic profile and the majority ICBM clients live above the national poverty line, yet they live perilously close to the edge of the poverty line. Using logistic regression, this study found that the higher the client’s income level, the higher the probability of their being selected in the program. This findings contradict with the existing Islamic microfinance literature that claim ICBM institutions in general could demonstrate a capacity to extend their services more widely to the poorest if Islamic charity is the main source of microfinance funding. This study suggests some possible barriers to include the poor in the microfinance including institutional selection policy and self exclusion factors.